Il prezzo della bellezza: i consumi femminili in Italia 1914-2008 - Cassamagnaghi, Silvia (Disuguaglianza e generazioni in Italia 1914-2008, 2026)
The status of women in Italy underwent profound changes from the beginning of 20th century to the early 2000s: women expanded their collective and individual expectations, taking on new roles, while their perception of themselves also changed. From a historical perspective, this article aims to trace the path taken by Italian women, analysing the development, adoption or adaptation to new models of consumption and mass culture, and observing how they have identified themselves, across generations and in relation to gender, through the analysis of certain long-term social and cultural dynamics; a path that has not always been linear, dictated by infinite variables, including the very idea of female beauty.